Cultural heritage in the fashion industry
1 online resource (220 pages)
Keywords: Exploring the intersection between traditional textile crafts and modern fashion practices, this book brings together leading scholars and practitioners to delve into how ancient techniques, designs and cultural heritage can inform and inspire sustainable innovation in the contemporary fashion industry. From revitalising unprotected crafts to integrating cultural symbols into modern apparel, the book provides a comprehensive look at how fashion can serve as a tool for preservation and progress.Each chapter presents case studies and practical examples from India and the Middle East, ranging from using eco-friendly materials and zero-waste practices to empowering marginalised communities through craft. This book is designed to equip readers with actionable insights, showcasing how tradition and innovation can create a more sustainable and equitable future for fashion.Drawing from a rich tapestry of interdisciplinary perspectives, Cultural Heritage in the Fashion Industry offers valuable insights for scholars of fashion and textiles, cultural studies, and anthropology in particular.